Effects of milk-derived bioactive peptide VPP on diarrhea of pre-weaning calves - Zong, Xiaomei; Gao, Ya; Du, Yufeng; Hou, Jinxiu; Yang, Linhai; Xu, Qingbiao (Frontiers in Veterinary Science, 2023)
A well-known milk-derived bioactive tripeptide, VPP (Val-Pro-Pro) has good anti-inflammatory, anti-hypertension, and anti-hydrolysis properties. However, whether VPP can alleviate calf intestinal inflammation is unclear. In this experiment, the effects of VPP on growth, diarrhea incidence, serum biochemical indices, short-chain fatty acids, and fecal microorganisms were examined in pre-weaning Holstein calves. Eighteen calves with similar birth date, body weight, and genetic background were randomly assigned equally to two groups (n = 9). The control group was given 50 mL of phosphate buffer saline before morning feeding, whereas the VPP group received 50 mL of VPP solution (100 mg/kg body weight/d). The study lasted for 17 days, with the first three days used for adaptation. Initial and final body weights were determined, and daily dry matter intake and fecal score were recorded throughout the study. Serum hormone levels and antioxidant and immune indices were measured on day 14. Fecal microorganisms were collected on days 0, 7, and 14, and 16S rDNA sequencing was performed. Oral administration of VPP did not significantly affect calf average daily feed intake and body weight, but the growth rate in body weight was significantly higher in the VPP group than in the control group on day 7 (P < 0.05). Compared with the control, VPP significantly decreased serum TNF-α and IL-6 contents (P < 0.05), and concentrations of nitric oxide and IL-1β also decreased but not significantly (0.05 < P < 0.1). After seven days of VPP, relative abundances of g_Lachnoclostridium, uncultured_bacterium_, and g_Streptococcus in fecal samples increased significantly (P < 0.05). Compared with the control, VPP significantly increased concentrations of the fecal short-chain fatty acids n-butyric acid and isovaleric acid (P < 0.05). In conclusion, VPP can relieve intestinal inflammation and alleviate the degree of diarrhea in pre-weaning calves.